Land reclamation using the horizontal drainage enhanced geotextile sheet method - Chen, Hao (2023)
Increasingly waste materials or soft soil dredged from sea or river have to be used as fill materials for land reclamation. Although preloading using prefabricated vertical drains (PVDs) has been commonly used as the treatment method for soft soil, this method is time consuming as it can only be applied after all the fill materials have been placed. In this paper, a conceptual design for land reclamation using a horizontal drainage enhanced geotextile sheet (HDeGs) method combined with vacuum preloading is proposed. Large-scale model tests are carried out to verify the effectiveness of the HDeGs method. The proposed method is also compared with the existing prefabricated horizontal drain (PHD) method and the advantages and disadvantages of the HDeGs with vacuum preloading method are discussed. This study has demonstrated that the proposed HDeGs method is not only effective, but also more efficient compared with the PVD or PHD methods, as it can reduce substantially the construction time required for land reclamation.